2008
DOI: 10.1016/j.ejcts.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Does endoesophageal ultrasound-guided fine-needle aspiration replace mediastinoscopy in mediastinal staging of thoracic malignancies?☆

Abstract: EUS-FNA sensitivity depends on the localisation of the primary tumour, and extent and location of mediastinal disease. For left-sided tumours, EUS-FNA improves mediastinal staging by assessing stations 5 and 6 inaccessible to conventional mediastinoscopy. For extended mediastinal disease, mediastinoscopy can be avoided or spared for restaging after neoadjuvant therapy. Exclusion of mediastinal involvement requires mediastinoscopy or open lymphadenectomy. Beyond mediastinal nodal staging, EUS-FNA may detect T4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…This high proportion is in concordance with other studies in which patients were included who were selected by CT or PET [4,9,12]. Our retrospective study thus confirms that EUS-FNA, as a minimally invasive alternative to surgical staging, reduces the need for surgical procedures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This high proportion is in concordance with other studies in which patients were included who were selected by CT or PET [4,9,12]. Our retrospective study thus confirms that EUS-FNA, as a minimally invasive alternative to surgical staging, reduces the need for surgical procedures.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study, a high EUS-FNA sensitivity was found for leftsided tumors [12]. Left-sided tumors predominantly metastasize to lymph node stations 4L and 7 that can accurately be assessed by EUS-FNA.…”
Section: Discussionmentioning
confidence: 97%
“…19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In a meta-analysis of 18 studies of EUS FNA for the mediastinal staging of lung cancer, sensitivity was 83% (95% confidence interval [CI], 78% to 87%) and specificity was 97% (95% CI, 96% to 98%). 39 In those patients with enlarged lymph nodes, sensitivity was 90% (95% CI, 84% to 94%).…”
Section: Accuracy Of Mediastinal Stagingmentioning
confidence: 98%
“…Unlike for other modalities, the sensitivity of EUS-FNA seems to be affected by variables such as node size, location of the tumor, and nodal station. One study showed that sensitivity can be as high as 91.7 % for bulky lymph nodes and as low as 43.8 % for nodes smaller than 1 cm on CT scan [32]. It was also shown that sensitivity for right-sided tumors (50 %) was lower than for left-sided tumors (96.6 %), and that sensitivity was highest (80.6 %) for station 7 and lowest (23.8 %) for station 4R.…”
Section: Eus-fnamentioning
confidence: 99%